Current basic and preclinical research for treatment of radiation therapy–induced hyposalivation - Olga J. Baker, DDS, PhD; Harim Tavares dos Santos, DDS, PhD; Kihoon Nam, PhD (JADA Foundational Science)
Objectives: Patients receiving radiation therapy (RT) for head and neck cancer experience hyposalivation, a condition that results in loss of oral health and significantly decreases the quality of life of millions of patients worldwide. Treatments include saliva substitutes and secretory agonists that provide only temporary relief and can result in significant adverse effects. To find more permanent and clinically viable solutions, alternative strategies are being developed that may restore salivary gland function in patients with head and neck cancer. This review provides an overview and basic interpretation of research for the treatment of RT-induced hyposalivation. Search Strategy: The authors critique and synthesize a broad group of approaches that promote secretory function in an irradiated salivary gland. Citation Sources: Three databases (PubMed, MEDLINE, Google Scholar) were searched for relevant peer-reviewed articles published from January 2000 through July 2024. Study Selection Criteria: The authors selected research constituting a continuum from the most to least studied approaches to treating RT-induced hyposalivation with the goal of facilitating future work in the field. Data Elements Included: The RT-induced hyposalivation treatments were categorized into post- and pre-RT headings, with approaches further distinguished according to their therapeutic goal, modality, and research stage, as well as with regard to their general pros and cons. Overall Conclusion: A summary of the research approaches used to treat RT-induced hyposalivation has been created to encourage the development of improved treatments.